THE BIBLE'S VIEWPOINT - Malika Uraimjonova Qahromon kizi (American Journals, 2023)
The article included the life span of women of the Dynasty, especially the queens, some of their political and social activity, and the development of diplomatic relations based on historical sources, the conclusions are explained.
Keywords: Timor-Leste Queens, DiplomaticK Relations, Palace Property Lady, Gavhar Shod Begim, Shodmulk Wife, Honzoda Begim Worldoro